Leptin in diabetic pregnancy. (16th November 2010) - Higgins, M; Russell, N; Brazil, D; McAuliffe, F
Abstract : Leptin is involved in the regulation of body weight. The aim of this study was to study maternal and cord leptin in non-diabetic, type 1 diabetic and type 2 (pregestational diabetic, PGDM) diabetic pregnancies. Prospective cohort study with maternal serum samples obtained at 36-week gestation and cord blood at delivery. Clinical data on both normal and PGDM pregnancies was obtained. Leptin was measured by enzyme-linked immunoassay (Human Leptin Immunoassay; R&D Systems, Minneapolis, Minnesota, USA). Non-parametric data were compared using Mann–Whitney or Kruskal Wallis tests. 40 women with T1DM, 10 women with T2DM and 30 non-diabetic women consented to the study. There was no difference in maternal body mass index (BMI) between the three groups. Infants of PGDM pregnancy had a higher birthweight centile. There was no difference in maternal leptin levels at 36-week gestation. Cord leptin was higher in infants of both T1DM (223 pg/ml (25.7–810 pg/ml)) and T2DM (447.2 pg/ml (136.3–679 pg/ml)) compared to infants of non-diabetic mothers (80.3 pg/ml (27.3–623.1 pg/ml)) (p<0.05). Among the PGDM group only third trimester HbA1c significantly related to cord leptin after controlling for birth weight, birthweight centile and maternal BMI (r=0.28, p=0.04). Infants of diabetic mothers may have some degree of leptin resistance, which could be have an important role in appetite regulation in extra-uterine life. This research reiterates the importance of tight glycaemic control in the third trimester of pregnancy in women with pregestational diabetes.